Effect of different drying techniques on physicochemical, thermal, and functional properties of seera. Issue 11 (18th August 2018) - Ahmad, Sameer; Nema, P. K.; Bashir, Khalid
ABSTRACT: Seera produced by different drying techniques was evaluated regarding its various physicochemical properties. The rheological properties of the batter showed a shear thinning behavior and Herschel–Bulkley model was best fitted with R 2  = 0.9987. The results revealed that water absorption capacity increased as compared to the wheat flour and maximum absorption was found in freeze-dried seera (1.91 g g −1 ), followed by oven-dried (1.62 g g −1 ) and sun-dried (1.13 g g −1 ). Oil absorption capacity of seera decreased as compared to wheat flour, with minimum values obtained for freeze-dried (0.93 g g −1 of seera). Carbohydrate content increased significantly in seera sample to 81.76%, while fat, protein, and moisture content decreased significantly. L* values increased significantly, while as both a* and b* values decreased. Bulk density also showed an increasing trend with maximum value in freeze-dried seera. Transition temperatures changed significantly for the seera samples along with enthalpy of gelatinization. Fourier transform infrared pattern did not change with drying.